Research on Simulink/Fluent Collaborative Simulation Zooming of Marine Gas Turbine. (2nd March 2017) - Wang, Zhi-tao; Li, Jian; Li, Tie-lei; Li, Shu-ying
Abstract : Based on the detailed analysis of collaborative running interface of Simulink/Fluent, a system simulation for the rated working condition as well as variable working condition of marine gas turbine has been achieved, which can improve the simulation efficiency of marine gas turbine by developing simulation model of combustor with Fluent and simulation models of other components with Simulink. The result shows that the Simulink/Fluent collaborative simulation zooming can make the inner working conditions of combustor be observed specifically, based on the overall performance matching analysis; thus an effective technical means for the structural optimization design of combustor has been provided.